Perancangan Aplikasi Mobile Zakat dan Infaq Berbasis Android Pada Baznas Kabupaten Tangerang - Imron Imron; Nurul Azizah; M Sinta Nurhayati; Bambang Wijonarko (Universitas Batanghari Jambi, 2021)
Science and Technology can be utilized in improving performance in an organization or company. During the COVID 19 Pandemic, BAZNAS Kabupaten Tangerang was encouraged to create a media as a facility for philanthropists in delivering zakat and infaknya, due to many limitations to be done directly as before. An application to receive and distribute zakat through android-based devices in the palm of the hand is the solution of the problem that can help BAZNAS Kabupaten Tangerang to be able to continue carrying out its activities. The result of this research is designing and building android-based applications in BAZNAS kabupaten Tangerang that are expected to be able to serve the community, store and share information to the community. Supported by articles, news, information documents, and discussion forums as a forum to increase trust and foster religious and religious values in the community.